Hints of Disk Substructure in the First Brown Dwarf with a Dynamical Mass Constraint - Alejandro Santamaría-Miranda; Pietro Curone; Laura Pérez; Nicolas T. Kurtovic; Carolina Agurto-Gangas; Anibal Sierra; Itziar de Gregorio-Monsalvo; Nuria Huélamo; James M. Miley; Aina Palau; Paola Pinilla; Isabel Rebollido; et al. (The Astrophysical Journal Letters)
We present high-resolution Atacama Large Millimeter/submillimeter Array (ALMA) observations at 0.89 mm of the Class II brown dwarf 2MASS J04442713+2512164 (2M0444), achieving a spatial resolution of 0 $\mathop{.}\limits^{^{′′} }$ 046 (∼6.4 au at the distance to the source). These observations targeted continuum emission together with ^12 CO (3–2) molecular line. The line emission traces a Keplerian disk, allowing us to derive a dynamical mass between 0.043 and 0.092 M _⊙ for the central object. We constrain the gas-to-dust disk size ratio to be ∼7, consistent with efficient radial drift. However, the observed dust emission suggests that a dust trap is present, enough to retain some dust particles. We perform visibility fitting of the continuum emission, and under the assumption of annular substructure, our best fit shows a gap and a ring at 98.1 ${}_{-8.4}^{+4.2}$ mas (∼14 au) and 116.0 ${}_{-4.8}^{+4.2}$ mas (∼16 au), respectively, with a gap width of 20 mas (∼3 au). To ensure robustness, the data were analyzed through a variety of methods in both the image and uv planes, employing multiple codes and approaches. This tentative disk structure could be linked to a possible planetary companion in the process of formation. These results provide the first dynamical mass of the lowest mass object to date, together with the possible direct detection of a substructure, offering new insights into disk dynamics and planet formation in the very low-mass regime. Future higher spatial resolution ALMA observations will be essential to confirm these findings and further investigate the link between substructures and planet formation in brown dwarf disks.